The Technology of Secure Data Processing in Production Systems Based on the Use of Special Microcontrollers - G. Magomedov., S.; ., . (International Journal of Engineering and Technology, 2018)
The technology is proposed to provide secure processing of data in technological systems based on the use of special microprocessors. A variant of the architecture of such a microprocessor is presented, as well as data processing algorithms that allow efficiently solving problems of secure data processing. The basis for the protection of data processing is the use of algorithms based on the sets of residual number systems (RNS). In the operative memory of the microprocessor, not the number, but the sets of its modules, are stored and processed. Therefore, stealing an intruder of a modules set does not allow him to recover the required number. The encryption keys for each microprocessor are formed together with other ones in the framework of a subsystem controlling other microprocessors, as well as the server.Â Â